Energy in Soil Failure under Different Boundry Conditions - Singh, Shashi Kumar; Wadhwa, D S (Journal of Agricultural Engineering, 2002)
A rectangular flat plane blade was operated at very slow speed in the soil under different boundary conditions to determine energy to peak force per unit volume of soil-deformed. Also the failure patterns were studied. Energy to peak force per unit volume of soil could be drastically reduced by limiting the soil ahead of the tool such that the bite length was less than that required for transitional zone to appear. At critical bite length the mode of soil failure abruptly changed from flat shear plane failure to logarithmic spiral plane failure.